Characterization of a second class Ie ribonucleotide reductase - Juliane John; Daniel Lundin; Rui M. Branca; Rohit Kumar; Vivek Srinivas; Hugo Lebrette; Martin Högbom (Communications Biology)
Abstract Class I ribonucleotide reductases (RNRs) convert ribonucleotides into deoxyribonucleotides under oxic conditions. The R2 subunit provides a radical required for catalysis conducted by the R1 subunit. In most R2s the radical is generated on a tyrosine via oxidation by an adjacent metal site. The discovery of a metal-free R2 defined the new RNR subclass Ie. In R2e, three of the otherwise strictly conserved metal-binding glutamates in the active site are substituted. Two variants have been found, VPK and QSK. To date, the VPK version has been the focus of biochemical characterization. Here we characterize a QSK variant of R2e. We analyse the organismal distribution of the two R2e versions and find dozens of organisms relying solely on the QSK RNR for deoxyribonucleotide production. We demonstrate that the R2eQSK of the human pathogen Gardnerella vaginalis (Bifidobacterium vaginale) modifies the active site-adjacent tyrosine to DOPA. The amount of modified protein is shown to be dependent on coexpression with the other proteins encoded in the RNR operon. The DOPA containing R2eQSK can support ribonucleotide reduction in vitro while the unmodified protein cannot. Finally, we determined the first structures of R2eQSK in the unmodified and DOPA states.